2021
DOI: 10.1371/journal.pone.0259130
|View full text |Cite
|
Sign up to set email alerts
|

A green-lipped mussel reduces pain behavior and chondrocyte inflammation and attenuated experimental osteoarthritis progression

Abstract: The green-lipped mussel (GLM) contains novel omega-3 polyunsaturated fatty acids, which exhibit anti-inflammatory and joint-protecting properties. Osteoarthritis (OA) is a degenerative joint disease characterized by a progressive loss of cartilage; oxidative stress plays a role in the pathogenesis of OA. The objectives of this study were to investigate the in vivo effects of the GLM on pain severity and cartilage degeneration using an experimental rat OA model, and to explore the mode of action of GLM. OA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…GLM in OA mice reduced nociception and the expression of proinflammatory cytokines (IL-1β, IL-6) and inducible nitric oxide synthase. It also exerted a chondroprotective effect by decreasing the production of chondrocyte-degrading enzymes (matrix metalloproteinase-3/13, ADAMTS5), and suppressing chondrocyte necroptosis [17]. These anti-arthritis/antiinflammatory effects of GLM are comparable to the nonsteroidal anti-inflammatory drug (NSAID) celecoxib, which is frequently used for OA [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…GLM in OA mice reduced nociception and the expression of proinflammatory cytokines (IL-1β, IL-6) and inducible nitric oxide synthase. It also exerted a chondroprotective effect by decreasing the production of chondrocyte-degrading enzymes (matrix metalloproteinase-3/13, ADAMTS5), and suppressing chondrocyte necroptosis [17]. These anti-arthritis/antiinflammatory effects of GLM are comparable to the nonsteroidal anti-inflammatory drug (NSAID) celecoxib, which is frequently used for OA [17].…”
Section: Discussionmentioning
confidence: 99%
“…It also exerted a chondroprotective effect by decreasing the production of chondrocyte-degrading enzymes (matrix metalloproteinase-3/13, ADAMTS5), and suppressing chondrocyte necroptosis [17]. These anti-arthritis/antiinflammatory effects of GLM are comparable to the nonsteroidal anti-inflammatory drug (NSAID) celecoxib, which is frequently used for OA [17]. Also, a clinical trial suggested that GLM may reduce pain and functional capacity in OA patients [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 99 Mussels, containing a large amount of 12% glycosaminoglycans, are a high source of a rare, potent form of omega-3 fatty acids (called eicosatetraenoic acid (ETA)), indicating the intense anti-inflammatory properties through inhibiting the enzyme-related pathways (cyclooxygenase and lipoxygenase-based paths) from producing inflammatory factors. 100 Interestingly, antioxidants in green-lipped mussels were proven to mediate the free radicals, which were the typical indicators in inflamed joints. 101 , 102 Therefore, a variety of injectable materials have been developed to fill the joint cavity, capable of inflammatory factor elimination especially in the liquid form.…”
Section: The Applications Of Mussel Biomimetic Materials In Msdsmentioning
confidence: 99%